Effect of Sodium Borohydride to Ferric Chloride Molar Ratios on Nanoscale Zero-Valent Iron for Hydrogen Generation from Formic Acid - Siti Aishah Yusuf; Meor Saiful Rizal Meor Ahmad Zubairi; Siti Fatimah Abdul Halim; Siu Hua Chang (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Hydrogen generation from formic acid using nanoscale zero-valent iron (nZVI) represents a promising route for low-cost and sustainable hydrogen production. However, the effect of sodium borohydride (NaBH₄) to ferric chloride (FeCl₃) molar ratio on nZVI synthesis and performance remains insufficiently explored. This study investigated how varying NaBH₄:FeCl₃ molar ratios affect nZVI synthesis characteristics and its hydrogen generation efficiency from formic acid, which acts as a safe and easily handled hydrogen carrier. nZVI was synthesized through a one-step liquid-phase chemical reduction method using NaBH₄:FeCl₃ ratios ranging from 4.4:1 to 8.8:1. UV–Vis spectroscopy indicated that the 4.4:1 ratio yielded the highest nZVI formation, reflecting optimal reduction efficiency and particle formation. Hydrogen generation experiments conducted in a closed reactor equipped with a water displacement system revealed that nZVI synthesized at the 4.4:1 ratio achieved the maximum hydrogen volume (98 mL), which progressively declined to 53 mL at the 8.8:1 ratio. These findings demonstrate that precursor molar ratios significantly influence nZVI formation, stability, and reactivity toward hydrogen evolution. An optimal NaBH₄:FeCl₃ ratio of 4.4:1 was identified for maximizing nZVI formation and hydrogen volume, providing valuable insights for developing scalable formic acid–based hydrogen generation systems. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).